Unexpected behavior of some nitric oxide modulators under cadmium excess in plant tissue - Kováčik, Jozef; Babula, Petr; Klejdus, Bořivoj; Hedbavny, Josef; Jarošová, Markéta (PloS one, 2014)
Various nitric oxide modulators (NO donors--SNP, GSNO, DEA NONOate and scavengers--PTIO, cPTIO) were tested to highlight the role of NO under Cd excess in various ontogenetic stages of chamomile (Matricaria chamomilla). Surprisingly, compared to Cd alone, SNP and PTIO elevated Cd uptake (confirmed also by PhenGreen staining) but depleted glutathione (partially ascorbic acid) and phytochelatins PC2 and PC3 in both older plants (cultured hydroponically) and seedlings (cultured in deionised water). Despite these anomalous impacts, fluorescence staining of NO and ROS confirmed predictable assumptions and revealed reciprocal changes (decrease in NO but increase in ROS after PTIO addition and the opposite after SNP application). Subsequent tests using alternative modulators and seedlings confirmed changes to NO and ROS after application of GSNO and DEA NONOate as mentioned above for SNP while cPTIO altered only NO level (depletion). On the contrary to SNP and PTIO, GSNO, DEA NONOate and cPTIO did not elevate Cd content and phytochelatins (PC2, PC3) were rather elevated. These data provide evidence that various NO modulators are useful in terms of NO and ROS manipulation but interactions with intact plants affect metal uptake and must therefore be used with caution. In this view, cPTIO and DEA NONOate revealed the less pronounced side impacts and are recommended as suitable NO scavenger/donor in plant physiological studies under Cd excess.
Keywords: Nitric Oxide Donors; fluorescenční mikroskopie; donory oxidu dusnatého; Antioxidants; cyklické N-oxidy; Microscopy, Fluorescence; Chamomile; reaktivní formy kyslíku; Glutathione; S-Nitrosoglutathione; Microscopy, Confocal; Seeds; heřmánek, heřmánkovec, rmen, rmenec; konfokální mikroskopie; antioxidancia; nitroprusid; semena rostlinná; Reactive Oxygen Species; Cadmium; Imidazoles; Cyclic N-Oxides; oxid dusnatý; glutathion; Nitroprusside; kyselina askorbová; Nitric Oxide; S-nitrosoglutathion; imidazoly; kadmium; Ascorbic Acid